PHARMACOVIGILANCE AND ITS RELEVANCE TO SIDDHA SYSTEM - MEENA R; RAMASWAMY R S (International Journal of Pharma and Bio Sciences, 2013)
Existence of Siddha system of medicine can be traced to ancient times. It has survived the onslaught of various other systems of medicines proving its efficacy. Siddhars were experts in medicine preparations which cured innumerable diseases. Pharmacovigilance is defined as the science of detection, assessment, understanding and prevention of adverse drug effects or any other possible drug related problems. Although the term pharmacovigilance is actually not featured in Siddha texts, it is vibrant throughout literature. This paper deals with the historical perspectives, adverse drug reactions in Siddha system, need for pharmacovigilance, challenges faced, pharmacovigilance of clinical trials, measures to improve pharmacovigilance of herbal medicines and future suggestions.